Seroepidemiological Studies of Arboviruses in Africa - (:unkn) unknown (My University, 2018)
The literature on sero-epidemiological studies of flaviviral infections in the African continent is quite scarce. Much of the viral epidemiology studies have been focussing on diseases such as HIV/AIDS because of their sheer magnitude and impact on the lives of people in the various affected countries. Increasingly disease outbreaks caused by arboviruses such as the recent cases of chikungunya virus, dengue virus and yellow fever virus have prompted renewed interest in studying these viruses. International agencies from the US, several EU nations and China are starting to build collaborations to build capacity in many African countries together with established institutions to conduct these studies. The Tofo Advanced Study Week (TASW) was established to bring the best scientists from the world to the tiny seaside town of Praia do Tofo to rub shoulders with African virologists and discuss cutting-edge science and listen to the work of researchers in the field. In 2015 the 1st TASW focussed on Ebola virus. The collections of abstracts from participants at the 2nd TASW which focused on Dengue and Zika virus as well as presentations on other arboviruses are collated in this chapter.
Keywords: African Research